Auditory Training Induces Asymmetrical Changes in Cortical Neural Activity - Tremblay, Kelly L; Kraus, Nina (Journal of speech, language, and hearing research, 2002)
Pre-attentive cortical evoked potentials reflect training-induced changes in neural activity associated with speech-sound training. Seven normal-hearing young adults were trained to identify two synthetic speech variants of the syllable /ba/. As subjects learned to correctly identify the two stimuli, changes in P1, N1, and P2 amplitudes were observed. Of particular interest is that P1, N1, and P2 components of the N1-P2 complex responded differently to listening training. That is, significant changes in P1 and N1 amplitude were recorded over the right but not the left hemisphere. In contrast, increases in P2 were observed bilaterally. These results indicate that training-related changes in neural activity are reflected in far-field aggregate neural responses and that distinct patterns of neural change, perhaps reflecting hemispheric specialization, likely represent different aspects of auditory function .